Can ischemia-modified albumin help in differentiating myocardial perfusion scintigraphy results? - Hüseyin Ede; Barış Yaylak; Süleyman Akkaya; Seyhan Karaçavuş; Ayşe Yeşim Göçmen; Ali Rıza Erbay (KARE Publishing, 2016)
Objective: Myocardial perfusion scintigraphy (MPS) is a diagnostic tool commonly used to detect significant coronary lesion. However equivocal, false negative or positive results can be yielded. Controversial findings regarding the role of ischemia-modified albumin (IMA) in MPS evaluation persist. The aim of the present study was to examine the role of serum IMA in the assessment of MPS results. Methods: MPS using technetium (99mTc) sestamibi and transthoracic echocardiography was performed on 62 consecutive subjects prospectively enrolled. Exercise treadmill test (ETT) with modified Bruce protocol was used to induce coronary ischemia. During MPS performance, blood samples for serum IMA were obtained at 3 times: at pre-exercise, at the peak of ETT, and 6 hours after ETT. Patients were classified into 3 groups according to MPS results (normal, equivocal, and ischemia). Results: Sixty-two patients (23 normal, 20 equivocal, 19 with ischemia) were included. Pre- and peak-exercise IMA values were similar among the groups (p=0.706 and 0.904). Postexercise IMA values of the normal and equivocal groups were similar (p=0.733), while that of the ischemia group was significantly higher than the values of either the normal (p<0.001) or equivocal groups (p<0.001). ΔIMA (the difference between post-exercise and peak-exercise IMA) of the ischemia group was significantly higher than that of either the normal (p<0.001) or equivocal groups (p<0.001). Conclusion: Serum IMA was found to be significantly increased in cases of ischemia on MPS. Subjects with normal and equivocal MPS had a similar pattern during the test. IMA may be used in differentiation of equivocal results from false positive results.